METADISCOURSE MARKERS IN ENGLISH ESSAYS WRITTEN BY INDONESIAN STUDENTS IN EFL SETTING - Rosyida Ekawati; Afiifah Al Rosyiidah (STKIP Siliwangi, 2022)
English essays commonly use metadiscourse markers to assist and direct readers in understanding the essays. This study aims at identifying and explaining interactive and interactional metadiscourse markers used by male and female students and their roles in the essays. There are 10 essays written by English Department students of second semester at the University of Trunojoyo Madura. The essays were written by male and female students with one of the assigned topics about diet for female and music for male students. This research was conducted as descriptive qualitative research methods, while to show the frequency of metadiscourse markers used by male and female students in the essays, simple quantification was done manually. Results show that both male and female use interactive metadiscourse markers in the essays that consist of transitions, frame markers, and code glosses, while interactional metadiscourse markers consist of hedges, boosters, attitude markers, self-mention, and engagement markers. Male students tend to use metadiscourse markers lower than female students but they use similar pattern of the markers. Only for self-mention items that is used higher by male students. The uses of metadiscourse markers have a significant role in organizing and producing of written essays to achieve certain communicative purposes.